2007
DOI: 10.1021/ja068964z
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy-Terminated Organic Semiconductor-Based Field-Effect Transistors for Phosphonate Vapor Detection

Abstract: Organic field-effect transistors (OFETs) with a hydroxy-functionalized semiconductor incorporated into a receptor layer were fabricated and shown to respond strongly to the analyte dimethyl methylphosphonate (DMMP) that simulates phosphonate nerve agents. Large and reproducible source-drain current changes were observed upon exposure to DMMP vapor. Compared to single component transistors, OFETs with a mixed hydroxylated and nonhydroxylated semiconductor upper layer exhibited higher sensitivity. We further inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
125
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 35 publications
4
125
0
Order By: Relevance
“…Precursor 2 as well as the tin compounds 3 and 6 were obtained by following literature procedures, while 5 is commercially available. [19][20][21][22] All synthesised materials exhibited good thermal stability with decomposition temperatures (5% weight loss) above 350 °C. More details of their thermal as well as electrochemical properties can be found in the Supplementary Information.…”
Section: Introductionmentioning
confidence: 99%
“…Precursor 2 as well as the tin compounds 3 and 6 were obtained by following literature procedures, while 5 is commercially available. [19][20][21][22] All synthesised materials exhibited good thermal stability with decomposition temperatures (5% weight loss) above 350 °C. More details of their thermal as well as electrochemical properties can be found in the Supplementary Information.…”
Section: Introductionmentioning
confidence: 99%
“…Organic field‐effect transistors (OFETs) have attracted considerable research attention due to their potential application for low‐cost, flexible, and wearable electronics 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. OPTs are an attractive category of OFETs, which can be used as photodetectors, light‐induced switches, light‐triggered amplifiers, and image sensors, amongst other applications 15, 16, 17, 18, 19, 20, 21, 22, 23.…”
mentioning
confidence: 99%
“…More recent work, however, has shown that proper modification of the semiconductor material can lead to more directed responses. For example, Huang et al (14) incorporated alkoxy side chains in an organic semiconductor layer and observed an improved response to phosphonate vapors compared to the alkyl-substituted material. Additionally, semiconductors modified with chiral, nonracemic amino acid groups were used for discrimination between citronellol enantiomers (15).…”
mentioning
confidence: 99%